Pengaruh Model Pembelajaran Problem Based learning terhadap Literasi Matematika Siswa SMAN 1 Lembar - Sri Hidayatullah; Sutarto Sutarto; Yuntawati Yuntawati (Lembaga Pusat Kegiatan Belajar Masyarakat (PKBM) Tunas Harapan, 2025)
The purpose of this study was to determine the effect of problem-based learning model on mathematical literacy of students of SMAN 1 Lembar. The method used in this research is quasi experimental method with Pretest-Posttest Control Group Design research design. The subjects of this research were students of class X SMAN 1 Lembar. The samples used in this study were two classes where class X 1 as the experimental class and X 2 as the control class, then the two classes were given different treatments, namely the experimental class was given treatment with a problem-based learning model while the control class was given a conventional learning model (lecture). After being given treatment, in the form of a pre-test, then a posttest is given to determine the final ability of students. The instrument used in this study is to use a test consisting of 3 essay-shaped questions. The analysis technique used is using t-test statistical analysis with the help of SPSS 25. From the results of the hypothesis test the sig value. (2-tailed) 0.000 <0.05 then H0 is rejected and H1 is accepted. So it can be concluded that there is an effect of problem-based learning model on students' mathematical literacy.